Clinical and dermoscopic features of nail apparatus pigmentations - Sobjanek, Michał; Michajłowski, Igor; Biernat, Wojciech; Włodarkiewicz, Adam; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Diagnosis of nail apparatus pigmentation is often a challenge. Some of the lesions are caused by presence of melanin (melanonychia), others by various non-melanin pigments (chromonychia). The most important is the connection of melanonychia with nail apparatus melanoma. It is established that melanonychia is the first symptom of malignancy in about 70% of patients. The diagnosis of nail apparatus melanoma is usually delayed and misdiagnosis is common, due to uncharacteristic clinical features and rare incidence in the Caucasian population. Objectives. Determination of the prevalence and nature of nail apparatus pigmentation in a northern Polish population and investigation of its clinical and dermoscopic features. Evaluation of the usefulness of dermoscopy in early diagnosis of nail apparatus melanoma. Material and methods . One thousand five hundred and eighty-eight patients with various nail apparatus pathologies who were referred to the Department of Dermatology, Venerology and Allergology, Medical University of Gdansk, from 2005 to 2010, were included in the study. Among these patients 185 cases of nail apparatus pigmentation were diagnosed. Diagnosis of melanonychia was established according to histopathological examination. Results . In 149/185 patients (80.54%) chromonychia and in 36/185 (19.46%) melanonychia were diagnosed. Statistically significant differences in skin phototype between patients with melanonychia and chromonychia were observed. The most common causes of chromonychia were subungual hematoma (54%) and onychomycosis (25%). In the majority of cases, melanonychia had a benign origin: benign hyperplasia (58%) and melanocytic nevus (28%). Nail apparatus melanoma was diagnosed in 2 cases (5%). There were statistically significant differences between chromonychia and melanonychia in clinical and dermoscopic features. Specific for melanonychia patterns were: brown background and lines. The dermoscopic pattern of nail apparatus melanoma differed from benign melanocytic lesions. In melanoma cases the dermoscopic pattern was characterized by a dark brown background and irregular in colour, width and parallel lines. Conclusions . According to clinical and dermoscopic examination it is possible to distinguish melanocytic (melanonychia) from non-melanocytic lesions (chromonychia). The dermoscopic pattern of nail apparatus melanoma differs from benign lesions. Dermoscopy is useful in early diagnosis of nail apparatus melanoma but biopsy is still the gold diagnostic standard.